Ferric Citrate Hydrate as a Phosphate Binder and Risk of Aluminum Toxicity - Ajay Gupta (MDPI AG, 2014)
Ferric citrate hydrate was recently approved in Japan as an oral phosphate binder to be taken with food for the control of hyperphosphatemia in patients with chronic kidney disease (CKD). The daily therapeutic dose is about 3 to 6 g, which comprises about 2 to 4 g of citrate. Oral citrate solubilizes aluminum that is present in food and drinking water, and opens the tight junctions in the intestinal epithelium, thereby increasing aluminum absorption and urinary excretion. In healthy animals drinking tap water, oral citrate administration increased aluminum absorption and, over a 4-week period, increased aluminum deposition in brain and bone by about 2- and 20-fold, respectively. Renal excretion of aluminum is impaired in patients with chronic kidney disease, thereby increasing the risk of toxicity. Based on human and animal studies it can be surmised that patients with CKD who are treated with ferric citrate hydrate to control hyperphosphatemia are likely to experience enhanced absorption of aluminum from food and drinking water, thereby increasing the risk of aluminum overload and toxicity.